4734 Sayılı Kamu İhale Kanunu Kapsamındaki İhalelerin İdari ve Yargısal Denetimi - Seyhan, Serkan (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Kamu Hukuku Anabilim Dalı, 2018)
4734 sayılı Kanun ile düzenlenmiş olan kamu ihalelerinin idari ve yargısal denetimi konusu bu çalışmanın kapsamını oluşturmaktadır. Çalışmanın amacı, serbest piyasa ekonomisinde kamu kaynaklarının verimli kullanımı ve yolsuzlukları önleme aracı olarak kurgulanan ihale sistemine ilişkin idari ve yargısal denetimin Türk hukukundaki düzenleniş biçimini, mevzuat hükümleri, öğreti ve yargısal içtihatlar ışığında incelemektir. Ayrıca bu çalışmada 4734 sayılı Kanun, ilgili Yönetmelikler, Kamu İhale Kurulu ve Danıştay kararları arası farklılıkları saptayarak ideal bir ihale denetim mekanizmasının oluşturulması için çeşitli öneriler ortaya koyulmaya çalışılmıştır.

The administrative and judicial review of the public procurement regulated by Law No. 4734 constitutes the scope of this work. The aim of the study is to examine and explain, in the light of legislative provisions, doctrines and judicial jurisprudence, reglements of Turkish law on administrative and judicial control of the public procurement system, which is designed as a means of preventing the corruption and efficient use of public resources in the free market economy. Besides, in this study, various suggestions were made to establish an ideal public procurement control mechanism by determining the differences between Law 4734 and related Regulations, Public Procurement Board and Council of State decisions.
The Administrative and Judicial Review of the Public Procurement Regulated By the Public Procurement Law No. 4734
Keywords: Hukuk; Law; Devlet ihale sistemi; State tender system; Kamu ihalesi; Public bidding